2005
DOI: 10.1029/2005gb002502
|View full text |Cite
|
Sign up to set email alerts
|

Glacial/interglacial changes in the isotopes of nitrate from the Greenland Ice Sheet Project 2 (GISP2) ice core

Abstract: The 15N/14N and 18O/16O ratios of nitrate in the Greenland Ice Sheet Project 2 (GISP2) (Summit, Greenland) ice core are much higher in ice from the last glacial period than in the pre‐industrial Holocene, despite the lack of a significant glacial/interglacial change in nitrate concentration. While both the 15N/14N and 18O/16O records are anticorrelated with snow accumulation rate, neither is satisfactorily explained by accumulation changes or post‐depositional processes. The similarity in the glacial/interglac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 88 publications
(175 reference statements)
3
55
0
Order By: Relevance
“…Freyer et al (1996) showed that nitrogen isotope composition in Antarctic NO − 3 was closely related to snow accumulation rate, with lower 15 N at higher accumulation sites. This result was later confirmed for Greenland ice (Hastings et al, 2005). For high accumulation sites, Hastings et al (2004) concluded that 15 N and 18 O of NO − 3 are related to atmospheric sources/processes, in particular NO x oxidation chemistry, rather than post depositional effects, a result also suggested by other studies (Alexander et al, 2004;Heaton et al, 2004).…”
Section: Sources Of Snowpack Nitratesupporting
confidence: 69%
“…Freyer et al (1996) showed that nitrogen isotope composition in Antarctic NO − 3 was closely related to snow accumulation rate, with lower 15 N at higher accumulation sites. This result was later confirmed for Greenland ice (Hastings et al, 2005). For high accumulation sites, Hastings et al (2004) concluded that 15 N and 18 O of NO − 3 are related to atmospheric sources/processes, in particular NO x oxidation chemistry, rather than post depositional effects, a result also suggested by other studies (Alexander et al, 2004;Heaton et al, 2004).…”
Section: Sources Of Snowpack Nitratesupporting
confidence: 69%
“…Profiles of nitrogen (oxygen) stable isotopes of NO Hastings et al, 2005;Jarvis et al, 2009) is discouraged, due to its sensitivity to post-depositional fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our new measurements, our goal is threefold: to show how isotopic measurements of nitrate can be used to study atmospheric processes operating on NO x , ozone and related trace gases, to assess the most likely controls over δ 15 N and Δ 17 O of nitrate, and in this regard to critically review current assumptions, and to identify most pressing needs in this research field. This has important implications in terms of interpreting the message carried by stable isotope ratios of ice‐core nitrate [ Alexander et al , 2004], in particular its δ 15 N signature [ Freyer et al , 1996; Hastings et al , 2005].…”
Section: Introductionmentioning
confidence: 99%